Experimental Study on Hydrothermal Carbonization of Lignocellulosic Biomass with Magnesium Chloride for Solid Fuel Production - Cubillos-Montecino, F; Diaz-Robles, L; Campos-Bravo, V; Vallejo-Gallardo, F (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The effect of magnesium chloride as an additive of hydrothermal carbonization (HTC) of lignocellulosic biomass (Pinus radiata sawdust) was studied. The HTC tests were carried out at fixed conditions of temperature and residence time of 220 °C and 1 h, respectively, and varying the dose of magnesium chloride in the range 0.0-1.0 g MgCl2/g biomass. The carbonized product (hydrochar) was tested in order to determine its calorific value (HHV) while using PARR 6100 calorimeter, mass yield by gravimetry, elemental analysis using a LECO TruSpec elemental analyzer, volatile matter content, and ash content were obtained by standardized procedures using suitable ovens for it. The results show that using a dose of 0.75 g MgCl2/g biomass results in an impact on the mass yield that was almost equal to change operating conditions from 220 to 270 °C and from 0.5 to 1 h, without additive. Likewise, the calorific value increases by 33% for this additive dose, resulting in an energy yield of 68%, thus generating a solid fuel of prominent characteristics. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.